Family influence on smoking habits among secondary school children, 1997 - Abdul Haris Muhammad; Khadijah Shamsuddin (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
In April 1997, a cross-sectional study was carried out in Kota Bharu Kelantan to determine family influence on smoking habits among male secondary school children. Parents and siblings smoking habits, family structure, parental supervision, communication between parents and child, parental education and occupation were among family factors that were studied in relation to students' smoking habit. Other factors include having friends who smoked, influence of cigarette advertisement, academic achievement and student's knowledge about the dangers of smoking. For this study, 460 male form four students were randomly selected from six secondary schools. However, 38 (8.3%) of them were not included in the analysis because they did not fill up important sections of the questionnaire. The prevalence of cigarette smoking among male secondary school children was 33.2%. Through crude analysis family factors, father's smoking habit (Odds Ratio 1.85, 95% C.I. 1.08-3.16), brother's smoking habit and lack of parental supervision were found to be significantly associated with students' smoking habit. Influence of cigarette advertisement, having friends who smoked, poor academic achievement and knowledge about the dangers of smoking were among the non-familial factors found to have significant association with students' smoking habits (p<0.05). Further analysis showed that the effect of father's smoking habit on students' smoking habit 'as still significant although other factors like cigarette advertisement, having friends who smoked and student's knowledge about the dangers of smoking were controlled Odds Ratio 1.87, 95% C.I 1.05-3.32). In conclusion, family influences especially father's smoking habit is an important factor that affects student's smoking habit and the models within the home need to be seriously considered in cigarette smoking prevention among adolescents.